PENGARUH INKUIRI TERBIMBING TERINTEGRASI PENDEKATAN DEEP LEARNING TERHADAP AKTIVITASDAN HASIL BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Prilly Rismawany; Destria Roza (Smart Education, 2026)
Abstract: This study aims to determine the effect of the guided inquiry model integrated with a deep learning approach on students’ learning activities and learning outcomes in the topic of electrolyte and nonelectrolyte solutions in grade XI at SMA Negeri 4 Medan. This research used a quantitative method with a population consisting of 12 classes of grade XI students. The sample was selected using random sampling, with class XI-7 as the experimental class and class XI-1 as the control class, consisting of 32 and 35 students, respectively. Data were collected through learning outcome tests and observation sheets of student activities that had been validated by experts. The data were analyzed using a one-tailed t-test. The results showed that students’ learning activities in the experimental class were higher than those in the control class, with a tvalue of 6.601 greater than the ttable value of 1.671. Learning outcomes also showed a significant improvement, with a tvalue of 2.304 greater than the ttable value of 1.671. In addition, there was a positive and significant correlation between students’ learning activities and learning outcomes, with a correlation coefficient of 0.885 (very high category) and a coefficient of determination of 78.3%. The n-gain analysis indicated a 69% improvement in learning outcomes, categorized as moderate. Therefore, the implementation of this learning model has a positive effect on students’ learning activities and outcomes. Keywords: Guided Inquiry, Deep Learning, Learning Activities, Learning Outcomes, Electrolyte and Nonelectrolyte Solutions Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model inkuiri terbimbing yang terintegrasi dengan pendekatan deep learning terhadap aktivitas dan hasil belajar siswa pada materi larutan elektrolit dan nonelektrolit di kelas XI SMA Negeri 4 Medan. Penelitian ini menggunakan metode kuantitatif dengan populasi seluruh kelas XI yang berjumlah 12 kelas. Sampel diambil secara random sampling, yaitu kelas XI-7 sebagai kelas eksperimen dan kelas XI-1 sebagai kelas kontrol, dengan jumlah siswa masing-masing 32 dan 35 orang. Pengumpulan data dilakukan melalui tes hasil belajar dan lembar observasi aktivitas siswa yang telah divalidasi oleh ahli. Analisis data menggunakan uji t satu pihak. Hasil penelitian menunjukkan bahwa aktivitas belajar siswa pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol, dengan nilai thitung 6,601 lebih besar dari ttabel 1,671. Hasil belajar siswa juga menunjukkan peningkatan signifikan dengan nilai thitung 2,304 lebih besar dari ttabel 1,671. Selain itu, terdapat hubungan positif dan signifikan antara aktivitas dan hasil belajar siswa dengan nilai korelasi 0,885 (kategori sangat tinggi) dan koefisien determinasi sebesar 78,3%. Hasil analisis n-gain menunjukkan peningkatan hasil belajar sebesar 69% dengan kategori sedang. Dengan demikian, model pembelajaran ini berpengaruh positif terhadap aktivitas dan hasil belajar siswa. Kata kunci: Inkuiri Terbimbing, Deep Learning, Aktivitas Belajar, Hasil Belajar, Larutan Elektrolit dan Nonelektrolit